ON SCIENTIFI C AND MEDICAL PERSONNEL TRAINING AT V.I. SHUMAKOV FEDERAL RESEARCH CENTER OF TRANSPLANTOLOGY AND ARTIFI CIAL ORGANS OF THE MINISTRY OF HEALTHCARE OF THE RUSSIAN FEDERATION (Вестник трансплантологии и искусственных органов)
On scientifi c and medical personnel training at V.I. Shumakov Federal Research Center of Transplantology and Artifi cial Organs of the Ministry of Healthcare of the Russian Federation